n Sistematisering van die industriele groeiproses van Italie, 1815-1960 - Van Huyssteen, Pieter Hillebrand (Stellenbosch : Stellenbosch University, 2012)
Skripsie (M. Com.) -- Universiteit van Stellenbosch, 1972.